2012
DOI: 10.1155/2012/790910
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Specific Immunotherapy with Hymenoptera Venoms Using Ultrarush Regimen in Children: Safety and Tolerance

Abstract: Background & Objective. Ultrarush induction for specific venom immunotherapy has been shown to be reliable and efficacious in adults. In this study its safety and tolerance in children was evaluated. Methods. Retrospective analysis of 102 ultrarush desensitizations carried out between 1997 and 2005 in 94 children, aged 4 to 15 years. Diagnosis and selection for immunotherapy were according to recommendations of the European Academy of Allergy and Clinical Immunology. Systemic adverse reactions (SARs) were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
(15 reference statements)
3
17
0
1
Order By: Relevance
“…According to Müller, grade systemic reactions of severity grades III and IV were very rare. A recent study in 94 children who were given a cumulative dose of 111.1 µg Hymenoptera venom over 210 min yielded similar results [15].Brehler et al compared the safety of different immunotherapy protocols and noted a significant reduction in the incidence of adverse effects when fewer subcutaneous injections were administered in the preliminary phase [2]. A number of investigations concerning the safety and tolerability of various immunotherapy protocols demonstrated results similar to those reported thus far [12,16].…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…According to Müller, grade systemic reactions of severity grades III and IV were very rare. A recent study in 94 children who were given a cumulative dose of 111.1 µg Hymenoptera venom over 210 min yielded similar results [15].Brehler et al compared the safety of different immunotherapy protocols and noted a significant reduction in the incidence of adverse effects when fewer subcutaneous injections were administered in the preliminary phase [2]. A number of investigations concerning the safety and tolerability of various immunotherapy protocols demonstrated results similar to those reported thus far [12,16].…”
mentioning
confidence: 61%
“…In general, side effect rates following specific immunotherapy are higher for bee venom than wasp venom. Side effect rates may be as high as 40% [15].However, a conclusive evaluation cannot be made yet because just a few systematic studies performed thus far in children permit a reliable comparison of different protocols in respect of their efficacy and tolerability.With due awareness of the fact that a child may demonstrate a serious reaction to an insect venom injection in rare cases, VIT should be initiated under constant observation and adequate emergency treatment should be available at all times. Even when treatment is continued on an out-patient basis, adequate emergency therapy should Maintenance therapy (100 µg) was administered after preliminary therapy as follows:…”
mentioning
confidence: 99%
“…Schwere, lebensbedrohliche systemische Reaktionen treten sehr selten auf [54,[197][198][199]. Gemäß den Daten aus dem Paul-Ehrlich-Institut (1991-2000) wurde eine Inzidenz an systematischen Reaktionen von 0,002-0,0076 % pro Injektion bei nichtmodifizierten Allergenextrakten und von 0,0005-0,01 % pro Injektion bei chemisch modifizierten Allergenextrakten (Allergoiden) errechnet [200].…”
Section: Sicherheit Risikofaktoren Und Unerwünschte Wirkungenunclassified
“…Ultrarush protocols also are effective in children but are associated with a significant risk of SARs. Köhli-Wiesner et al [41] demonstrated that SARs occur in 16% of children treated with a 1-day ultrarush protocol for honeybee or wasp hypersensitivity and the authors concluded that the risk of a SAR is similar to that seen in comparable adult ultrarush protocols. The authors recommend that if ultrarush protocols are considered for use in children that they be initiated in an inpatient intensive care unit for appropriate monitoring.…”
Section: Selection Of Venoms and Treatment Protocolsmentioning
confidence: 99%